Brexit and Gibraltar: the Spanish proposal for joint sovereignty (Spanish Yearbook of International Law, 2016)
The result of the referendum held in the United Kingdom on 23 June 2016, which favoured withdrawal from the European Union, marked the entry into a new legal and political context which will have important consequences not only for the UK, but also for the EU and all its Member States. In this scenario, Brexit and Gibraltar are intimately connected, so that the United Kingdom’s departure from the Union would have profound consequences for Gibraltar. The most obvious consequence is that the withdrawal of the United Kingdom from the Union will inevitably produce the withdrawal, too, of Gibraltar, since the legal tie established by Article 355.3 TEU will disappear. In fact, there is no legally-acceptable justification for seeking ‘precedents’ by reference to micro-States or to the notion of ‘reverse Greenland’ to bring about the chimera that Gibraltar could remain within the Union even if the United Kingdom were no longer a Member State. Besides, as Gibraltar is the object of a dispute over sovereignty, over which the Union has no jurisdiction, the bilateral Spanish-British approach should be scrupulously respected in the negotiations held between the EU and United Kingdom regarding the ‘sovereignty issue’. In this context, the Spain’s proposal for shared sovereignty, presented by the IV UN Committee on 4 October 2016, could be a good deal for all or at least could be a good starting point for negotiation.